ANALISIS GAYA BELAJAR SISWA KELAS VII DALAM MEMAHAMI MATERI FIQIH THAHARAH DI SMPS IT SULTHONIYAH SAMBASTAHUN PELAJARAN 2023-2024 - Adekni Adekni; Oskar Hutagaluh; Muspian Muspian (CV. ADIBA AISHA AMIRA, 2024)
This thesis discusses students' learning styles in understanding thaharah fiqh material at SMPS IT Sulthoniyah Sambas. This research has three research objectives including the following; First, to find out the understanding of class VII students at SMPS IT Sulthoniyah Sambas. Second, to find out what the learning styles of class VII students are in the Thaharah fiqh subject at SMPS IT Sulthoniyah Sambas. Third, to find out the evaluation of the learning outcomes of class VII students on fiqh thaharah material at SMPS IT Sulthoniyah Sambas. This research uses a descriptive qualitative approach. This type of research is field research (filed research). There are three types of data collection techniques in this research, namely: observation, interviews, and documentation. Meanwhile, the data analysis techniques used are data reduction, data presentation, verification and drawing conclusions. Then the data validity checking techniques used are source triangulation and technical triangulation. The results of the research are: regarding analysis of student learning styles in understanding fiqh thaharah material at SMPS IT Sulthoniyah Sambas. Students' understanding in the learning process of thaharah fiqh material, namely regarding students' understanding, is quite good. Class VII students prefer the kinesthetic learning style, namely learning by practicing directly related to the material and being helped to explain by the teacher, this has a positive impact on students. The learning outcomes of class VII students after the teacher carried out the evaluation were improved and all were above average or KKM. With the kinesthetic learning style that the teacher has implemented, this can make students more active compared to just explaining the material.